Modulation of T helper 1 and T helper 2 immune balance in a murine stress model during Chlamydia muridarum genital infection. - Tesfaye Belay; Elisha Martin; Gezelle Brown; Raenel Crenshaw; Julia Street; Ashleigh Freeman; Shane Musick; Tyler J Kinder (PLoS ONE)
A murine model to study the effect of cold-induced stress (CIS) on Chlamydia muridarum genital infection and immune response has been developed in our laboratory. Previous results in the lab show that CIS increases the intensity of chlamydia genital infection, but little is known about the effects and mechanisms of CIS on the differentiation and activities of CD4+ T cell subpopulations and bone marrow-derived dendritic cells (BMDCs). The factors that regulate the production of T helper 1 (Th1) or T helper 2 (Th2) cytokines are not well defined. In this study, we examined whether CIS modulates the expressions of beta-adrenergic receptor (β-AR), transcription factors, hallmark cytokines of Th1 and Th2, and differentiation of BMDCs during C. muridarum genital infection in the murine model. Our results show that the mRNA level of the beta2-adrenergic receptor (β2-AR) compared to β1-AR and β3-AR was high in the mixed populations of CD4+ T cells and BMDCs. Furthermore, we observed decreased expression of T-bet, low level of Interferon-gamma (IFN-γ) production, increased expression of GATA-3, and Interleukin-4 (IL-4) production in CD4+ T cells of stressed mice. Exposure of BMDCs to Fenoterol, β2-AR agonist, or ICI118,551, β2-AR antagonist, revealed significant β2-AR stimulation or inhibition, respectively, in stressed mice. Moreover, co-culturing of mature BMDCs and naïve CD4+ T cells increased the production of IL-4, IL-10, L-17, and IL-23 cytokines, suggesting that stimulation of β2-AR leads to the increased production of Th2 cytokines. Overall, our results show for the first time that CIS promotes the switching from a Th1 to Th2 cytokine environment. This was evidenced in the murine stress model by the overexpression of GATA-3 concurrent with elevated IL-4 production, reduced T-bet expression, and IFN-γ secretion.